1-[2-(1H-Benzimidazol-2-yl)ethyl]-1H-1,2,3-benzotriazole - Zhong Zhang; Wei Lu; Difeng Wu (Acta Crystallographica Section E, 2011)
In the title compound, C15H13N5, the N-containing heterocycles are linked by an ethylene spacer in a gauche conformation, the N—C—C—C torsion angle along the linker being 60.1 (3)°. The dihedral angle between the terminal benzotriazole and benzimidazole rings is 39.02 (6)°. In the crystal, adjacent molecules are connected by N—H...N hydrogen bonds, forming an infinite chain along the c axis. π–π stacking interactions [centroid–centroid distance = 3.8772 (7) Å] between the benzotriazole rings of neighbouring chains extend these chains into a supramolecular sheet in the bc plane. Weak intermolecular C—H...N interactions further stabilize the crystal structure.